DAMPAK IMPLEMENTASI KEBIJAKAN AKSES E-RESOURCES DI PERPUSTAKAAN PERGURUAN TINGGI DELIMA JAKARTA - Fauziah, Kiki (BACA: Jurnal Dokumentasi dan Informasi, 2016)
This article analyzes the impacts of the policy implementation on e-resources access at Jakarta Delima Academic Library. The aim of the research is to analyze the impacts regarding the new policy of e-recources access at Jakarta Delima Academic Library to its users. This research was used qualitative approach with case studies. Data collection for this research was conducted through interview, observation and literary study. The result shows that the impacts caused by the new policy are it does not meet the user needs of information, the ineffectiveness of the e-resources use, and the loss of the essence of e-resources in the library.